Spontaneously occurring lesions in uvea, retina, lens and optic nerve in eyes of sheep and goats - SANGAMWAR, U Y; PARIHAR, N S; SHARMA, A K (The Indian Journal of Animal Sciences, 2013)
Systematic study of ocular structures in sheep and goaFs revealed occurrence of lesions in uvea, retina, lens and opticnerve. The pathological conditions observed were persistent pupillary membrane, retinal congestion, retinal degeneration,retinal detachment, optic neuritis, aphakia, lenticular opacity and lenticular disfigurement.